URGENSI KONSELING TEMAN SEBAYA DI PONDOK PESANTREN: SEBUAH META ANALISIS [THE URGENCY OF PEER COUNSELING IN ISLAMIC BOARDING SCHOOLS: A META-ANALYSIS] - Saputro, Nurul Fitrian Eko; Isnaini, Subi Nur; Casmini, C (Acta Islamica Counsenesia: Counselling Research and Applications, 2023)
This paper wants to provide a mapping of the urgency of peer counseling services in the Islamic boarding school environment. Using qualitative research methods with a meta-analysis approach to analyze the content of previous studies. The results of this study are Showing a mapping of the importance of implementing peer counseling or peer counseling in terms of the point of view of students, pesantren managers, and kiai who are elements of pesantren. This argument is built by seeing that pesantren are one of the institutions that still need to be optimized for the application of counseling services. Seeing the complexity of existing problems, especially those experienced by students.